2017
DOI: 10.1515/popets-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Device Tracking: Measurement and Disclosures

Abstract: Internet advertising and analytics technology companies are increasingly trying to find ways to link behavior across the various devices consumers own. This cross-device tracking can provide a more complete view into a consumer's behavior and can be valuable for a range of purposes, including ad targeting, research, and conversion attribution. However, consumers may not be aware of how and how often their behavior is tracked across different devices. We designed this study to try to assess what information abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 10 publications
2
53
0
Order By: Relevance
“…In general, tracking can be understood as an analytic procedure with a user-centric view where personal and behavioral data are collected and aggregated to a detailed, person-specific profile [3,15]. A number of studies revealed that user behavior can be traced back even across multiple devices and that different websites pass on user information to third parties [7,[15][16][17].…”
Section: Theoretical Framework 21 Consequences Of Tracking On User mentioning
confidence: 99%
“…In general, tracking can be understood as an analytic procedure with a user-centric view where personal and behavioral data are collected and aggregated to a detailed, person-specific profile [3,15]. A number of studies revealed that user behavior can be traced back even across multiple devices and that different websites pass on user information to third parties [7,[15][16][17].…”
Section: Theoretical Framework 21 Consequences Of Tracking On User mentioning
confidence: 99%
“…PII leaks enable trackers to potentially attach identities to browsing histories. More recent work includes detection of PII leakage to third parties in smartphone apps [34,40], PII leakage in contact forms [38], PII leakage that enables cross-device tracking [12], and data leakage due to browser extensions [39].…”
Section: Related Workmentioning
confidence: 99%
“…This is an area for future work. Finally, our own approach is most similar to that of Brookman et al [12] and Starov et al [39] who test combinations of encodings and/or hashes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few straightforward mitigations that merchants could deploy: (1) enabling HTTPS on all shopping (and especially payment-related) pages -this would protect against network adversaries, but not third-party trackers, our main adversary of interest (2) generating Bitcoinaddress QR codes internally instead of outsourcing it to a third party; (3) avoiding leaks of the Bitcoin address from payment receipt pages; and (4) avoiding unintentional PII leaks. As to the last point, however, note that the attack succeeds as long as some first party website visited by the user leaks PII to third parties, and at least some PII leakage is for crossdevice linking purposes [24], and thus intentional. Beyond these obvious steps, merchants could share less data with third parties, and with fewer of them, but this would come at the expense of their advertising and analytics objectives.…”
Section: Mitigation and Discussionmentioning
confidence: 99%